Distortion of Subjective Probabilities as a Reaction to Uncertainty - Fellner, William (Quarterly Journal of Economics, 1961)
I. Observation of slanted probabilities and computation of the correction factor, 670. — II. The question of rationality, 677. — III. Two small experiments, 686.